2009
DOI: 10.1016/j.jbusres.2008.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Managing anti-consumption in an excessive drinking culture

Abstract: A major contemporary challenge facing governments and health professionals is that of promoting sustainable and healthy approaches to alcohol consumption in a context where excessive alcohol consumption is the dominant trend [Plant M., Plant M., Binge Britain: the need for courage. Alcoholis 2006; 25, 3: 1.]. This article reports the results of a qualitative study examining the experiences of Higher Education students in the United Kingdom who are identifiable as anti-consumers because of their opposition to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 28 publications
8
104
1
3
Order By: Relevance
“…This said, the socially demanding aspects of being a non-drinker illustrated here and elsewhere (Piacentini & Banister, 2009;Seaman & Ikegwuonu, 2010) suggest that the availability and dependability of such friendships might be particularly important or pertinent to individuals who must consistently defend the counter-normative position which they occupy through not drinking alcohol. In this way, the status of 'not drinking' seemed to provide a benchmark for our participants enabling (or forcing) them to assess the viability of particular social networks or individual friendships.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This said, the socially demanding aspects of being a non-drinker illustrated here and elsewhere (Piacentini & Banister, 2009;Seaman & Ikegwuonu, 2010) suggest that the availability and dependability of such friendships might be particularly important or pertinent to individuals who must consistently defend the counter-normative position which they occupy through not drinking alcohol. In this way, the status of 'not drinking' seemed to provide a benchmark for our participants enabling (or forcing) them to assess the viability of particular social networks or individual friendships.…”
Section: Discussionmentioning
confidence: 74%
“…For example, infrequent drinkers are included alongside nondrinkers by some authors (Nairn et al, 2006), while others integrate light and non-drinkers within the category 'anti-consumers' -orientating their enquiry towards individuals understood to operate outside of student norms more generally (Piacentini & Banister, 2009). …”
Section: Sampling Approach and Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, it would have aided Chikere and colleague to discover why 52.1% of those sampled declared that they will not quit episodic drinking despite being aware of the consequences of harmful consumption. This is because MacNeela and Bredin's (2011) study in Ireland, Beccaria & Sande's (2003) study of Norway and Italy and others from Denmark that utilised qualitative methods reported similar findings, and this has been attributed to many factors, one such being the growing culture of intoxication among young people (Piacentini and Banister 2009) who see drunkenness as a resource as well as social capital (Demant and Järvinen 2010). Denscombe (2008) argued that ''researchers use mixed methods to improve the accuracy of their data, whereas others use it to produce a more complete picture by combining information from complementary kinds of data sources'' (p.272).…”
Section: Discussion and Conclusion The Necessities Of Mixed Methods Dmentioning
confidence: 90%